2013
DOI: 10.1159/000348340
|View full text |Cite
|
Sign up to set email alerts
|

Can Breast Nipple Fluid Collected with Automated Aspiration and Preserved in Based-Liquid Solution Improve the Cytological Samples?

Abstract: Objective: Samples from breast nipples collected with the automated HALO™ Mamo Cito Test were studied in order to evaluate the cellularity for the diagnosis of breast cancer. Study Design: One hundred and fifty-nine asymptomatic women were prospectively examined. Women younger than 18 years, pregnant or lactating women, and women with a history of breast cancer, with previous radio- or chemotherapy and with nipple piercing were excluded from the study. Nipple samples from both breasts were collected. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Subgroup analyses and updates on the previously studied populations were identified through original study method descriptions, provided references, or direct confirmation by the study author. One most informative article was selected to represent the cohorts that were studied more than once to avoid double-counting the study subjects, leaving 16 articles for analysis of incidence of cytological groups (Figure 1) 12, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Eight of the 16 articles reported information on cancer outcomes (Table 2) 12, 17,18,23,[29][30][31][32] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subgroup analyses and updates on the previously studied populations were identified through original study method descriptions, provided references, or direct confirmation by the study author. One most informative article was selected to represent the cohorts that were studied more than once to avoid double-counting the study subjects, leaving 16 articles for analysis of incidence of cytological groups (Figure 1) 12, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Eight of the 16 articles reported information on cancer outcomes (Table 2) 12, 17,18,23,[29][30][31][32] .…”
Section: Resultsmentioning
confidence: 99%
“…The next most cited systems were the NCI FNA criteria and 12,18 articles, respectively. The rest of the articles either used other classification systems 20,31 , or did not provide any specific information about the source of the classification system 21,29 . The baseline characteristics of the included studies are shown in Supplemental Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There was a high rate of unsatisfactory samples, suggesting that the lack of standardization when preparing smears can be decisive in the loss of quality of the cells. In cases classified as atypical, it was difficult to observe some important nuclear characteristics, such as hyperpigmentation marked irregularity of the nuclear membrane due to virtue of the degree of degeneration of the smears [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Its potential as a screening tool for nipple fluid and has been evaluated by several groups. [23][24][25][26][27][28] However, the evidence base for the relative risk of breast cancer following abnormal cytology comes largely from breast tissue fine needle aspirate cytology or breast biopsies. [29][30][31] Whether the two can be compared is controversial.…”
mentioning
confidence: 99%